2020
DOI: 10.1186/s12885-020-06816-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific impact of patterns of imageable tumor growth on survival of primary glioblastoma patients

Abstract: Background: Sex is recognized as a significant determinant of outcome among glioblastoma patients, but the relative prognostic importance of glioblastoma features has not been thoroughly explored for sex differences. Methods: Combining multi-modal MR images, biomathematical models, and patient clinical information, this investigation assesses which pretreatment variables have a sex-specific impact on the survival of glioblastoma patients (299 males and 195 females). Results: Among males, tumor (T1Gd) radius wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Clinically, sex-specific patterns of tumor growth, measured via imaging, have also been identified by Whitmire et al 66 They demonstrate that tumor cell diffuse invasion rate is negatively correlated with survival in females but not males, while the size of the tumor overall is correlated with survival in males but not in females. Furthermore, male incidence bias has been seen clinically in both high- and low-grade brain tumors in data from six different countries with tumors such as astrocytomas, oligodendrogliomas, ependymoma, and medulloblastoma.…”
Section: Discussionmentioning
confidence: 70%
“…Clinically, sex-specific patterns of tumor growth, measured via imaging, have also been identified by Whitmire et al 66 They demonstrate that tumor cell diffuse invasion rate is negatively correlated with survival in females but not males, while the size of the tumor overall is correlated with survival in males but not in females. Furthermore, male incidence bias has been seen clinically in both high- and low-grade brain tumors in data from six different countries with tumors such as astrocytomas, oligodendrogliomas, ependymoma, and medulloblastoma.…”
Section: Discussionmentioning
confidence: 70%
“…Most previous studies have focused on the effect of different EOR on survival time ( 3 , 44 , 45 ), with fewer findings on how to select resection scopes in different populations and patients with different tumor characteristics at the same time. Among the important characteristics on the basis of which the model recommended different EOR, age ( 46 ), sex ( 47 ), tumor size ( 48 ), and crossing the midline ( 49 ) were considered to interact with EOR in the prognosis of patients with GBM in previous studies; that is, the effect of EOR on survival outcome was specific to the above variables. As for the tumor location and laterality, the finding that patients with tumors located in the right frontal lobe are more suitable for SpTR is consistent with the recent expert consensus ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that basal ganglia iron levels may be a useful biomarker in glioma prognosis ( 89 ). Advanced MR imaging techniques already have the potential to predict the influence of sex on GBM outcomes ( 16 , 90 ). Finally, on PET/CT, 68 Ga tracer uptake was found to correlate to brain tumor grade, with the ability to distinguish between low and high grade, as well as between grade III and IV, gliomas ( 91 ).…”
Section: Discussionmentioning
confidence: 99%